The Implementation of Total Physical Response Method with Pictures to Enhance Students’ Vocabulary and Creativity - Al-Farisi, Nizar Ahmad; Ismil Mubarok; Fitrah Yuliawati; Slamet; Mohammad Jusak (Journal of Studies in Academic, Humanities, Research, and Innovation, 2025)
This research explores the effectiveness of incorporating picture with the Total Physical Response (TPR) technique to improve vocabulary acquisition and creative thinking in EFL learners. A total of 36 second-grade students took part in two Classroom Action Research (CAR) cycles at SMAN 03 Pamekasan. The low average mark of 58 on the pre-test among students and early observations suggested significant challenges with vocabulary retention, spelling pronunciation and proper usage. TPR integration of movement and language acquisition was paired with writing activities. While introducing vocabulary words during the first cycle students worked together in groups to describe pictures in photos and include images and vocabulary words during the second cycle to increase memory. Although there was a 12.1% increase during the period of the study the outcomes did not meet the minimum passing criteria established by the institution (KKM). During the immediate cycle, additional practice and stress-relief techniques, such as occasionally reviewing images from recent tests, led to a significant improvement, with the average score increasing to 80. The research indicated that when paired with melodies, the TPR method enhanced students' vocabulary fluency, spelling, pronunciation, and accuracy of usage. Furthermore, it fostered greater student involvement, enthusiasm, and creativity in the classroom. Overall, the study demonstrates that TPR and picture provide an engaging, straightforward method for vocabulary acquisition, helping students navigate difficulties in language learning and fostering a more vibrant and enjoyable educational atmosphere.